A phenomenological study of the health-care related spiritual needs of multicultural Western Australians - Hawley, Georgina (Curtin University, 2002)
This study was designed to identify the spiritual needs of multicultural Australians with a health problem, in order to understand the educational implications for health care professionals. The rationale for the research was supported by the Australian Council for Health Service (1997) requirement that health care professionals meet the spiritual needs of their patients and clients'. At the commencement of this study, no research had been published on what these spiritual needs might be. To discover what health care professionals needed to be taught in order to meet the spiritual needs of their patients, I required a suitable group of patients. Then, after identify their spiritual needs, I wanted to explore ways in which these needs could be met. For this to occur, I also needed to identify factors that would fulfill patients' spiritual needs or prevent them from being met. This research proceeded in two stages. The first involved collecting data from all spiritual groups in Western Australia. The second involved the recruitment and interviewing a small number of ex-patients to gain their perspective of health care related spirituality and needs. To gain data about the various spiritual groups in Western Australia, I wrote to all organisations and associations, asking for information and reference material. This data was analysed using HyperResearch (1995), and themes common to all spiritual groups were developed. The inter-relationship between these themes provided the framework for an emergent model of spirituality.For the second part of the research which involved a case study of health care patients, a qualitative methodology was used. This approach enabled me to explore the phenomenon of spirituality from the perspective of eight participants, which involved identifying their spiritual needs, the care they desired, and the rite of passage they underwent when receiving health care. The qualitative methodology enabled me to explore the subject from a sensitive holistic perspective, and to protect the integrity of the participants. I wanted to know what patients understood about their spirituality and how spiritual care could be implemented not only in clinical practice but also into health care education programs. The participants' detailed subjective experience was especially important, because I wanted to know how they identified their spiritual needs, how they had requested their needs be met by health care professionals, and the extent to which health care professionals had reacted to those cues. I formulated an 'interpretive phenomenology research' design based on the philosophical writings of Heidegger and Bakhtin. Heidegger argued that people gain knowledge of a subject from their own subjective experience, and of the person being in their world (simultaneous past, present and future thoughts). Bakhtin stated that to bring about social change, the researcher needed to understand the social context of the people's language including their culture, politics, government-provided amenities (such as education and health care), employment and social interaction, both within and outside their communities in which they live. The eight participants were interviewed a number of times in order to explore the phenomenon of spirituality beyond the notions already published in the literature (i.e. from multicultural Australian's perspective).They told of hospital or health care experiences that included: health care for childbirth, mental and psychiatric illnesses (depression, manic-depression, and anxiety), immunology (lymphoma), stroke, detoxification of alcohol, arthritis, coronary occlusion, hypertension, and peritonitis; surgical procedured/s such as repair of hernia, bowel obstruction, eye surgery, orchiopexy (removal of testes from inguinal canal into the scrotal sac), caesarian birth, appendectomy, and oophorectomy (removal of ovaries); treatments such as radiotherapy, chemotherapy, and physiotherapy; and hospital experiences in both large and small public and private acute hospitals, private and public mental health/psychiatric hospitals, intensive care and coronary care units. These situations demonstrate the diversity of contexts which people want their spiritual needs met. The study revealed that it is not only dying patients who have spiritual need; spiritual needs exist in widespread ordinary conditions and across a wide range of health care services. The eight participants - Ann, Athika, Garry, Red, Rosie, Scarlet, Sophie, and Tom (pseudonyms) - were drawn from many of the multicultural groups resident in Western Australia including Aboriginal, Chinese, English, European, Indian, and Irish peoples. Their spiritualities encompassed Judeo-Christian, Buddhist, Hindu, Pagan Romany, Society of Friends (Quaker), Humanist, Socialist, and Communist values and beliefs. The results of the research give insight into the eight participants' perspectives on being a person, their understanding of spirituality, perceived spiritual needs, their desired levels of spiritual care, and the rite of passage they experienced when undergoing health care treatment in hospital.The participants' spiritual needs comprised of four categories: 'mutual trust', 'hope', 'peace' and 'love'. The levels of spiritual care spoke of desiring were: 'acknowledgement', 'empathy', and 'valuing'. Recommendations are given for health care professionals to provide spiritual care for the eight participants, and implications are considered for the spiritual education of future health care professionals in order to sensitise them to the wide range of healthcare related spiritual needs they might encounter in local multicultural communities. It is recognised that the scope of the implications is contingent on further research establishing the incidence of health-care related spiritual needs among the broader population of multi-cultural Western Australians. The richness and depth of the data and the very sensitive nature of the material that came from the eight people who shared their experiences with me has rendered this thesis an important document. The nature of the various incidents and situations they shared with me, I believe, demonstrated their preparedness to tell their story so that health care can be improved. On many occasions, I felt honoured that they had sufficient trust in me to enable them to report such deep and personal suffering. For example, Rosie told me of her mental torment and of not knowing if she was alive or dead; of how she burnt her legs to try to feel pain in order to see if she was alive. It was stories such as this that gave me the passion to write this thesis well in order to do justice to all people who want spirituality included in health care treatment.